2001
DOI: 10.1111/j.1745-4514.2001.tb00751.x
|View full text |Cite
|
Sign up to set email alerts
|

ROLE OF pH IN GEL FORMATION OF WASHED CHICKEN MUSCLE AT LOW IONIC STRENGTH

Abstract: This work was designed to test the hypothesis that it is not solubilization of the myofibrillar proteins per se that is required to form good gels at low salt concentrations, but the protein‐containing structures must be disorganized. Gels were made from washed minced chicken breast muscle at 0.15, 0.88, and 2.5% sodium chloride. The gels made with varying salt concentrations were evaluated either at pH 6.0–6.5 or pH 7.0–7.4. Strain values, an indicator of protein quality, were high only at neutral pH in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…It has been described that this feature is species dependent (Perez-Mateos and Lanier 2006) and that it is enhanced by the pH-shifting method. It has been suggested (Chang et al 2001;Wright and Lanier 2005) that the more thorough disruption of muscle structure by acid or alkaline processing may play a key role in better distributing proteins for heat-induced gel formation which reduces the need for salt to accomplish the same effect. Kristinsson and Hultin (2003a) found that acid-and alkali-treated cod myofibrillar proteins gelled at lower temperatures than native proteins.…”
Section: Gel Qualitymentioning
confidence: 97%
“…It has been described that this feature is species dependent (Perez-Mateos and Lanier 2006) and that it is enhanced by the pH-shifting method. It has been suggested (Chang et al 2001;Wright and Lanier 2005) that the more thorough disruption of muscle structure by acid or alkaline processing may play a key role in better distributing proteins for heat-induced gel formation which reduces the need for salt to accomplish the same effect. Kristinsson and Hultin (2003a) found that acid-and alkali-treated cod myofibrillar proteins gelled at lower temperatures than native proteins.…”
Section: Gel Qualitymentioning
confidence: 97%
“…Gelling properties of the MPs depend upon pH (Chang and others 2001a; Lesiów and Xiong 2001a). At the isoelectric point (pI), proteins have a net charge of zero and retain the least amount of water.…”
Section: Phmentioning
confidence: 99%
“…Recent trends indicate many consumers are interested in reducing their sodium intake. Thus, the salt content of surimi seafood deserves considerable attention (Chang and others 2001).…”
Section: Introductionmentioning
confidence: 99%